STUDENT SATISFACTION OF ISLAMIC RELIGIOUS EDUCATION STUDY PROGRAM WITH THE EDUCATION PROCESS AT STAI ALHIKMAH JAKARTA - Taufik Abdillah Syukur (Jurnal Studi Islam Lintas Negara (Journal of Cross-Border Islamic Studies), 2022)
The purpose of this study was to determine the level of student satisfaction of the Islamic Religious Education Study Program towards the educational process at STAI ALHIKMAH Jakarta. This research uses the descriptive qualitative method. The conclusion of this study shows that the majority of students of the Islamic Religious Education Study Program are very satisfied with the educational process at STAI ALHIKMAH Jakarta.